A Novel Electrically Small Meandered Line Antenna with a Trident-Shaped Feeding Strip for Wireless Applications - Xueyao Ren; Xing Chen; Kama Huang (International Journal of Antennas and Propagation)
A novel electrically small antenna (ESA) which based on the meandered line structure is designed, fabricated, and measured. The proposed antenna whose total size is 13.50mm×13.51mm×0.8mm is designed to cater for the ISM (industrial, scientific, and medical) band of 2.45 GHz with a 𝑆11<−10dB bandwidth of 3.9%. By introducing a trident-shaped feeding strip and inserting 4 pairs of triangular slot stubs at the central feed line, the resonant frequency of the antenna drops to 2.45 GHz from 2.50 GHz and the impedance matching is improved significantly. The dimension parameters of this antenna are optimized to achieve wide impedance bandwidth, reasonably high gain, as well as omnidirectional radiation pattern.